(untitled) (ShodhVarta, 2024)
This study analyses the struggle for supremacy between the Parliament and the Supreme Court, the two important pillars of Indian democracy. It explains how the Constitution has granted specific powers and authority to these two institutions, thereby creating mutual balance and competition. The study cites various historical examples, such as the Kesavananda Bharati case and the 42nd Constitutional Amendment, which make it clear that at times the Parliament has challenged the decision-making power of the Court, while the Court has defined the limits of Parliament through its judicial review. As a result of this struggle, there arises the need for a continuous dialogue to uphold the Constitution and protect civil rights. In conclusion, it states that for a healthy democracy, it is essential to maintain a balance between the Parliament and the Supreme Court to remain effective in their respective functions